Australian surfers' awareness of 'surfer's ear'. Issue 1 (24th February 2020) - Simas, Vini; Hing, Wayne; Pope, Rodney; Climstein, Mike
Abstract : Objectives: To assess awareness of external auditory exostosis (EAE) among Australian surfers. Methods: This is a cross-sectional observational study, assessing professional and recreational Australian surfers. Currently, active surfers over 18 years of age, surfing year-round, were eligible to participate. After initial screening, individuals were asked to complete a questionnaire. All included volunteers underwent bilateral otoscopic examination, to assess the presence and severity of EAE. Results: A total of 113 surfers were included in the study and were divided into two groups, based on surfing status: 93 recreational surfers and 20 professional surfers. Recreational surfers were significantly older (p<0.005), more experienced (greater years surfing; p<0.005), with lower prevalence of otological symptoms (p<0.05). The most common symptoms were water trapping, impacted wax and hearing loss. Prevalence of EAE was high for both groups (95% in the professional surfers and 82.8% in the recreational surfers); however, recreational surfers had mild grade EAE (grade 1) as the most common presentation, as opposed to professionals who had severe grade EAE (grade 3) as the most common presentation (p<0.05 between groups). Awareness of the term 'surfer's ear' was high for both groups, as was knowledge of prevention options. However, fewer considered the condition to be preventable, and an even lower number reported regular use of prevention methods. Conclusion: Australian surfers had a high level of awareness of EAE; however, few reported using prevention methods, despite having a high prevalence of the condition. Health practitioners should screen susceptible individuals in order to recommend appropriate preventive measures.